Analyzing Students’ Perspective on Duolingo Application for English Daily Learning - Astuti, Widya (Journal of Language, Literature and Teaching, 2025)
This study explores the perspectives of non-English major university students on the use of the Duolingo application as a daily English learning tool. Conducted at IAIN Takengon with 25 students of Tourism department, the study employed a qualitative descriptive method. Students were instructed to use Duolingo regularly for one month and report their learning activity daily. Data were collected through open-ended questionnaires, interviews, and documentation, then analyzed thematically. The findings revealed that Duolingo helped improve students’ motivation, vocabulary, and grammar understanding; supported habit formation; offered flexible and personalized learning experiences; and increased students’ confidence. In addition, its game-like interface made the learning process enjoyable. This research provides insight into how mobile learning applications can support student engagement and offers practical recommendations for integrating technology into non-English major language instruction.Keywords: Perspective, Duolingo, IAIN Takengon